Zika virus preferentially replicates in the female reproductive tract after vaginal inoculation of rhesus macaques - Timothy D. Carroll; Ming Lo; Marion C. Lanteri; Joseph Dutra; Katie R. Zarbock; Paola Paz Silveira; Tracy Rourke; Zhong-Min Ma; Linda Fritts; Shelby L. O’Connor; Michael P. Busch; Christopher J. Miller (2017)
Zika virus (ZIKV) is a mosquito-transmitted virus that can cause severe defects in an infected fetus. ZIKV is also transmitted by sexual contact, although the relative importance of sexual transmission is unclear. To better understand the role of sexual transmission in ZIKV pathogenesis, a nonhuman primate (NHP) model of vaginal transmission was developed. ZIKV was readily transmitted to mature cycling female rhesus macaque (RM) by vaginal inoculation with 104–106 plaque-forming units (PFU). However, there was variability in susceptibility between the individual RM with 1–>8 vaginal inoculations required to establish infection. After treatment with Depoprovera, a widely used contraceptive progestin, two RM that initially resisted 8 vaginal ZIKV inoculations became infected after one ZIKV inoculation. Thus, Depoprovera seemed to enhance susceptibility to vaginal ZIKV transmission. Unexpectedly, the kinetics of virus replication and dissemination after intravaginal ZIKV inoculation were markedly different from RM infected with ZIKV by subcutaneous (SQ) virus inoculation. Several groups have reported that after SQ ZIKV inoculation vRNA is rapidly detected in blood plasma with vRNA less common in urine and saliva and only rarely detected in female reproductive tract (FRT) secretions. In contrast, in vaginally inoculated RM, plasma vRNA is delayed for several days and ZIKV replication in, and vRNA shedding from, the FRT was found in all 6 animals. Further, after intravaginal transmission ZIKV RNA shedding from FRT secretions was detected before or simultaneously with plasma vRNA, and persisted for at least as long. Thus, ZIKV replication in the FRT was independent of, and often preceded virus replication in the tissues contributing to plasma vRNA. These results support the conclusion that ZIKV preferentially replicates in the FRT after vaginal transmission, but not after SQ transmission, and raise the possibility that there is enhanced fetal infection and pathology after vaginal ZIKV transmission compared to a mosquito transmitted ZIKV.